(untitled) (Torani Journal of Fisheries and Marine Science, 2019)
The consequence of super intensive shrimp farming is an increase in aquaculture waste and disease transmission. Vibrio sp. Bacteria is a disease-causing agent in shrimp larvae when the shrimp is in a state of stress and weakness, and can cause death. The application of probiotics, namely beneficial microorganisms can degrade organic matter, reduce disease, and help accelerate the process of nutrient cycles as a consequence of super intensive shrimp farming. Commercial probiotics currently available are a mixture of several types of beneficial microorganisms, namely Bacillus sp., Pseudomonas sp., Nitrosomonas sp., Aerobacter sp., and Nitrobacter sp. The purpose of this study was to evaluate the use of probiotics with different time intervals to produce a decrease in the population of Vibrio sp. The research method applied was the treatment of commercial probiotics at different intervals of three, five, and seven days and without the administration of probiotics as controls. Furthermore, the bacterial population was calculated by total plate count (TPC). The results showed that the administration of probiotics had a significant effect on the decrease in the population of Vibrio sp. Provision of probiotics three days apart showed a decrease in the number of bacterial populations that were significantly different from the controls, but the same as the administration of intervals of five and seven days. The decrease in the number of bacterial populations in the treatment interval of three, five, and seven days in a row is 0.05 x , 0.41 x , and 0.61 x CFU / ml. This study recommends that the use of commercial probiotics intervals of seven days for super intensive vaname shrimp farming. The use of probiotics for three days indicates an impact on the increase in expenditure costs for probiotics. Commercial probiotic studies modified with natural microorganisms are thought to be able to streamline the operational costs of shrimp farming. Keywords: Vibrio sp. bacteria, probiotics, vaname shrimp, super intensive cultivation